Socio-cultural context-based inquiry learning in a mathematics flipped classroom - Cortez, Carlo P. (Animo Repository, 2024)
The research stands with the proposition that, if the students find learning realistic, interactive, and convenient, then the learning achievement and attitudes of the students will improve. The study incorporated sociocultural context in the activities while students engage with course content outside of class and the class time focuses on cooperative problem-solving, which combined cultural relevance and technology-enhanced learning. In addition, the study investigated the effects of the intervention in the students’ mathematics critical thinking attitude, attitude towards self-directed learning, and their mathematics performance under the topics of Functions. The findings indicated that students have significantly improved their scores as showed from the compared result of the pre-test and post test of researcher-made test. Morever, significant changes in the self-directed learning attitude of the students under the intervention was evident from their pre-test and post test. However, critical thinking attitude and self-directed learning attitude results from pre-tests and post-tests of the conventional group and the critical thinking attitude of the group under the intervention failed to reveal significant changes. It was recommended to have a similar study across all discipline simultaneously for one term as indicated and implied by the result of the scores of the students in mathematics critical thinking attitude assessment and attitude towards self-directed learning assessment and supported by the learners’ reflections during their period of the intervention.